Development of Phylum Mollusca Picture Cards as Learning Media - Akhsaniyah, Siti Mahrifatul; Sulistiyawati (Proceeding International Conference on Science and Engineering, 2021)
Abstract: The process of remembering, understanding, and mastering the concept of material can be done more interestingly through pictures. Pictures can have a positive impact in helping the child’s learning process in memory skills and can improve communication skills. This study aims to determine the feasibility level of the picture cards that have been developed. the research method used is research and devolopment (R&D). Research on the development of Phylum Mollusca picture cards using the application microsoft word and microsoft power poin. Medium assessment was carried out by one material expert, one medium expert, five peer reviewers, one biology teacher as a reviewer, and 15 grade x students. Meanwhile, the results of development research indicate that the quality of the invertebrates picture cards developed is in the very good category (SB) according to material experts with an ideal percentage of 89.33%, Good category (B) according to medium experts with an ideal percentage of 77.17%, Very good category (SB) according to peer reviewers with an ideal percentage of 90.8%, and biology teachers 86%. Thus it can be concluded that this media is declared fit for use as a medium for learning biology.